The Crime of Unauthorized Broadcasting on the High Seas - Nouf Abdalla Aljasmi (Journal of Legal Sciences, 2024)
The research paper investigates the complex world of illegal broadcasting on the high seas, examining the antecedents, legal frameworks, jurisdictional difficulties, and international cooperation crucial in tackling this complex issue. Unauthorized broadcasting offers serious risks, ranging from disruption of authorized broadcasts to intellectual property violations, raising awareness across the globe and especially the countries affected by the broadcasts. The analysis starts by tracking the development of unauthorized broadcasting throughout history. It revolves around the starting point when it came to be recognized as a treaty crime by international accords. It highlights the difficulties of jurisdiction and the need for comprehensive legal systems by illuminating the crucial role that flag states play in managing ships at sea. The work uses review of various material, including legislative frameworks at the international, regional, and domestic levels.